Implementasai Pembelajaran Perilaku Pencegahan Penyalahgunaan Narkoba Dalam Pendidikan Jasmani - Brio Alfatihah; Tarpan Suparman; Aang Solahudin Anwar (Jurnal Sekolah Dasar, 2019)
Indonesia is a drug emergency, yes, this sentence illustrates the current condition of the Indonesian Replubic State. This is caused by rampant drug trafficking and abuse. In Indonesia, data from the National Narcotics Agency of the Republic of Indonesia shows in 2004 that 15% of Indonesia's population was involved in drug abuse (3.2 million) and in 2005 showed that 15,000 people died each year due to drugs (Jakarta Provincial Narcotics Agency, 2009) . The latest data on drug abuse in 2014 has increased by 4 million (BNN, 2015). Do not rule out the possibility of drug abuse will continue to increase in the following years as long as there is no education on the dangers of drug education at the Secondary School level Education is believed to solve the problem of the Indonesian people in order to avoid drug abuse. This belief is strengthened because education is a planned effort to influence others, whether individuals, groups, or the community, so that they do what is expected by education practitioners (Notoatmodjo, 2003: 16). In addition, in RI Law No. 20 of 2003 concerning the National Education System, article 1. Explains that: "Education is everything that is done by someone for himself or done by someone else for him, with the aim of bringing him closer to the level of perfection" From the opinion of some experts and based on the Act –Chief The National Education System can overcome drug abuse behavior. While the education chosen by researchers is Physical Education. This consideration was chosen because in the Syllabus of learning in schools in Physical Education subjects there is some material regarding drug abuse itself. In addition to previous considerations, Physical Education not only aims to encourage physical growth, but as Freeman (2007: 27-28) states that physical education uses physical activity to produce overall improvements to the physical, mental and emotional quality of students as one complete unity. Through sports physical education and health it is expected that students become "physically educated people" who not only emphasize motor skills and movement patterns but can maintain health improvement as stated by Metzler (2005: 14) a person can become "Physically educated person" must meet the following standards: (1) demonstrate motor skills and the skills and patterns of motion needed to display various physical activities, (2) demonstrate an understanding of the concepts of motion, principles, strategies and tactics as they apply in learning and performance of various physical activities, (3) participate regularly in physical activities, (4) achieve and maintain improved health and fitness levels, (5) demonstrate personal and social responsibility in the form of respect for self and others in an atmosphere of activity s physical, and (6) values physical activity for health, pleasure, challenges, self-expression, and social interaction. Therefore the author tries to examine implementing a program to prevent drug abuse behavior in physical education. So physical education, sports and health can be one way or a protector to increase knowledge of the importance of preventing drug abuse